Blue lily, lily Blue [compact disc, unabridged] - Stiefvater, Maggie, 1981- (Stiefvater, Maggie, 1981- Raven cycle, 2014)
Blue Sargent has found things. For the first time in her life, she has friends she can trust, a group to which she can belong. The Raven Boys have taken her in as one of their own. Their problems have become hers, and her problems have become theirs. The trick with found things though, is how easily they can be lost.